Dexamethasone, oxaliplatin and cytarabine (R-DHAOx) as salvage and stem cells mobilizing therapy in relapsed/refractory diffuse large B cell lymphomas. Issue 1 (2nd January 2020) - Manconi, Lorenzo; Coviello, Elisa; Canale, Filippo; Giannoni, Livia; Minetto, Paola; Guolo, Fabio; Clavio, Marino; Marcolin, Riccardo; Cea, Michele; Cagnetta, Antonia; Gobbi, Marco; Miglino, Maurizio; et al.
Abstract: Cisplatin-containing salvage regimens followed by autologous hematopoietic stem cell (HSC) transplantation are the current standard of care for relapsed or refractory (R/R) lymphomas. We retrospectively analyzed efficacy and stem cell mobilizing activity of oxaliplatin, cytarabine, dexamethasone and rituximab (R-DHAOx) in 53 R/R diffuse large B cell lymphomas (DLBCL) treated in our center (median lines 2, range 2-5; median age 59, range 22–79). Hematological toxicity was manageable and no patients experienced renal impairment. After 2 courses the overall response rate was 60% (CR 49%, PR 11%). Median overall survival (OS) was 30.53 months (95% CI 11.5–49.55), 3-year OS 40.5%. Twenty-two eligible patients collected HSC and transplantation was performed in 21/22 patients (95%), after a median of 52 days from last cycle. Our results suggest that in DLBCL R-DHAOx has an excellent stem cell mobilizing capability, response rate comparable to cisplatin-containing regimens and good toxicity profile.